From cities to super mega city regions in China in a new wave of urbanisation and economic transition: Issues and challenges. (February 2020) - Yeh, Anthony Gar-On; Chen, Zifeng
A mega city region comprises a cluster of highly networked urban settlements anchored by one or more large cities. Substantial studies have been conducted in the 21st century to theorise the development of mega city regions from two perspectives: one focuses on the rationale/challenges of planning and governance while the other focuses on the economic forces that generate the mega city regions. In China, the outstanding position of mega city regions in China's economic development has been accentuated in both academic research and recent policies. Recent studies have unpacked the political dynamics of mega city regions in China and identified challenges for planning and governance. The present study approaches this issue through another theoretical lens and deciphers the economic process underneath the recent upsurge of Chinese mega city regions. By unfolding the economic transition since the late 1970s to trace the footprints of mega city region development, the paper contributes a discourse of how different waves of economic transition – that is, rural industrialisation, land-centred development and urban tertiarisation – have been steering individual cities towards super mega city regions. The paper also identifies the distinctive challenges confronting the future development of China's mega city regions, including jurisdictional fragmentation, socio-spatial inequality and environmental externalities, which were created because of the strong bottom-up initiatives in land development during rural industrialisation. New policies and planning are required in response to these challenges as well as to the emerging new industries in the new wave of economic transition (i.e. from labour-intensive industries to the development of high-tech industries).